Judicial behavior and devolution at the Privy Council - Sofia Amaral-Garcia; Nuno Garoupa (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In this article, we study judicial behavior at the Judicial Committee of the Privy Council (JCPC). British judges in general, and British high court judges in particular, are perceived to be independent and isolated from political pressure and interference. Furthermore, these judges tend to show a particularly high rate of consensus. This has led many scholars to consider that, contrarily to what holds for several other courts around the world (such as the US Supreme Court), the attitudinal model does not find support when British higher court judges are considered. In this paper we assess whether similar conclusions might be drawn from the JCPC, another British court of last resort. We create a unique dataset to study empirically decisions of the JCPC and investigate the extent to which judges exhibit different judicial behavior depending on the type of appeal being brought to the court, i.e., Commonwealth, devolution and domestic appeals. Our results indicate a higher polarization of judicial behavior in the context of devolution appeals (as measured by separate opinions). We discuss these results in the context of the comparative judicial behavior literature and the role of courts in the common law world (with particular reference to human rights).
Keywords: K0; 330; Judicial Committee of the Privy Council; British higher court judges; judicial behavior; devolution cases; Commonwealth cases; separate opinions; human rights